1981
DOI: 10.1002/jsfa.2740320211
|View full text |Cite
|
Sign up to set email alerts
|

Determination of soya proteins in food using an enzyme‐linked immunosorbent assay procedure

Abstract: Classical immunoanalytical techniques are based on native antigens and their precipitation with specific antibodies: they are not very appropriate for the investigation of processed denatured mixtures. This report describes an immunoassay based on the more recent but well-established enzyme-linked immunosorbent assay (ELISA) procedure, which in this case is specific for soya proteins that have been solubilised in urea and then 'renatured' by removing or diluting the denaturant. Levels of soya protein 100 g-I t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…The 7S fraction was chosen as the antigen because it presents higher immunogenicity and greater immunogenic stability than 11S (Tukur et al, 1996), although the content thereof is smaller. Hitchcock et al (1981) produced anti-protein antiserum from renatured soy protein, which responded more strongly to the 7S fraction and showed immunogenic resistance to denaturation. Gri$ths et al (1984) tested various commercial kits for quantifying soy in meat products, and found that all performed best with 7S.…”
Section: Characterization Of Soy As An Antigen and Of The Anti-soy Amentioning
confidence: 97%
See 2 more Smart Citations
“…The 7S fraction was chosen as the antigen because it presents higher immunogenicity and greater immunogenic stability than 11S (Tukur et al, 1996), although the content thereof is smaller. Hitchcock et al (1981) produced anti-protein antiserum from renatured soy protein, which responded more strongly to the 7S fraction and showed immunogenic resistance to denaturation. Gri$ths et al (1984) tested various commercial kits for quantifying soy in meat products, and found that all performed best with 7S.…”
Section: Characterization Of Soy As An Antigen and Of The Anti-soy Amentioning
confidence: 97%
“…The standard indirect ELISA method was developed on the basis of the reports of Hitchcock et al (1981), Ravestein and Driedonks (1986), Rittenburg et al (1987) and Medina (1988), with the objective of optimizing the working routine.…”
Section: Indirect E¸isamentioning
confidence: 99%
See 1 more Smart Citation
“…Physicochemical methods (López-Tapia et al, 1999) and immunochemical methods (e.g., Hitchcock et al, 1981;Griffiths et al, 1984;Rittenburg et al, 1987, Yasumoto et al, 1990Macedo-Silva et al, 2001;Heppell et al, 1987;Brandon et al, 1991;Bando, et al, 1998) have been described. However, so far, the methods are not sensitive enough.…”
Section: Soymentioning
confidence: 99%
“…However, most reliable methods are based on detection of soy protein or DNA. Protein based methods includes, electrophoretic or serologic (ELISA) methods [7][8][9] while PCR is most widely used as DNA based methods [4,10] . Because DNA is more stable to processing conditions than protein, PCR methods are shown to be more reliable when used in processed foods [10] .…”
Section: Introductionmentioning
confidence: 99%